Area grown with table grape (Vitis vinifera L) under protected cultivation and pest management practices used by growers in Caxias do Sul, RS Diagnóstico da área cultivada com uva fina de mesa (Vitis vinifera L) Sob Cobertura plástica e do manejo de pragas - Formolo R. (2011)
The area grown with table grapes (Vitis vinifera) under protected cultivation, pests associated with the crop and control strategies were surveyed using interviews with growers in Caxias do Sul, RS. During 2008/2009 season, it was identified 43 growers producing table grapes in an area of 30,36 ha. Itália cultivar responds for 70,31% of the area grown in the municipality. The major insect pests associated with Italia cultivar in the region was thrips Frankliniella rodeos Moulton and the South American Fruit Fly Anastrepha fraterculus (Wied). Pest management in based mainly on chemical control sprayed in a calendar based schedule. Major difficulties found to implement an integrated pest management in the protect grape cultivation in the region are the reduced technical assistance, confidence on tools for pest monitoring and reduced number of active ingredients authorized for insect control on grapes.